The Influence of Leadership and Motivation on Employee Performance (A Case Of Employees In The Kiaracondong Bandung City) - Apriyani Rahayu, Yani; Ridwan, S.; Febrian, Feby (Siber Journal of Advanced Multidisciplinary, 2024)
The purpose of this study was to find out and analyze: (1) Leadership (2) Work Motivation; (3) Employee Performance; and (4) The Influence of Leadership and Work Motivation on Eployee Performace a Case Employees in Kiaracondog SubDistrict, Bandung, both simultaneously and partially. The method of this research is descriptive survey and explanatory survey, the unit of analysis in this study is the employees in the Kiaracondong Subdistrict, Bandung with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Leadership in the Kiaracondong Subdistrict it turned out that most of the employees responded well enough; Employee work motivation in Kiaracondong Subdistrict in general can be said to be good; Employee performance in the Kiaracondong Subdistrict is currently considered good. Leadership and Work Motivation simultaneously affect the Employee Performance in the Kiaracondong Subdistrict. But partially dominant leadership influences performance rather than work motivation. Because Leadership is more dominant in influencing Performance, leadership being the first priority in improving Employee performance in Kiaracondong Subdistrict Environment .The leader turns out to contribute greatly to the improvement of employee performance. Abstracts are written in one paragraph using standard Indonesian with enhanced spelling. Maximum 200 words, using Times New Roman font size 12, space 1, Italic. Contains a brief description of the overall results of the study including background issues, objectives, methods, results and conclusions. Avoid writing bibliography citations, as well as abbreviations in the abstract. The abstract contains the title of the article, research object, objectives, methods and results. Abstracts written in Bahasa and English.